Analysis of Intercultural Communication Models Among UINSU FIS Students - Dhea Adelina Harahap; Febri Shaleh Siregar; Rizky Ananta; Maulana Andinata Dalimunthe; Hasan Sazali (Penerbit Jurnal Indonesia, 2022)
This study aims to determine the intercultural communication in question is the process of communication between groups of different cultures between foreign students and UINSU FIS students. This research uses descriptive research, which means a systematic, factual, and accurate description of the facts, characteristics and relationships between the phenomena being investigated. Research that uses descriptive type is research that is intended to describe, describe, or explain the state of the object being studied as it is about the analysis of intercultural communication in students of FIS UINSU. This research results that there is a KAB model for Aceh and Javanese students involving a mediator. This model illustrates that differences in communication behavior cause Papuan students to have difficulty adapting to Javanese students so that effective KAB is difficult to achieve. Therefore, the presence of a mediator from Javanese students is needed to bridge communication with Javanese student groups as well as to be a companion in class.